Oral cholera vaccine coverage evaluation survey: Forcibly Displaced Myanmar Nationals and host community in Cox's Bazar, Bangladesh - Qayum, Md. Omar; Billah, Mallick Masum; Sarker, Mohammad Ferdous Rahman; Alamgir, A. S. M.; Nurunnahar, Mehejabin; Khan, Manjur Hossain; Salim Uzzaman, M.; Henderson, Alden; Shirin, Tahmina; Flora, Meerjady Sabrina (Frontiers in Public Health, 2023)
Introduction: Cholera remains a significant public health concern in many parts of the world, especially in areas with poor sanitation and hygiene. Bangladesh and other impoverished nations have been severely affected by cholera outbreaks, especially in areas with a high population density. To mitigate the spread of cholera, oral cholera vaccines (OCVs) are recommended as a prophylactic measure. In May 2018, two doses of OCV ShancholTM were given to the Forcibly Displaced Myanmar Nationals (FDMN) in the registered and makeshift camps and the residents in the host community in Cox’s Bazar, Bangladesh because the conditions in the area favor transmission of cholera and other waterborne diseases. The goal of this study is to assess the OCVs coverage among the FDMN and host community in Cox's Bazar and identify reasons why people did not get vaccinated. Methods: In August 2018, we enrolled 4,240 respondents for this study. We used the "World Health Organization (WHO) Vaccination Coverage Cluster Surveys: Reference Manual (2018)" to conduct a coverage survey with three strata of the population: the host community from the Teknaf Upazilla, the registered camp, and the makeshift camp from the Ukhia Upazilla. We collected information regarding the OCV coverage, demographic characteristics, and knowledge and behaviors toward the vaccine. The data were analyzed using descriptive statistics. Results: According to our study, the overall OCV coverage was 85% with 68% in the host community, 91% in the registered camp, and 98% in the makeshift camp. The lower coverage in the host community was due to residents not knowing about the vaccination campaign, unavailability of vaccines, and not knowing where to go for vaccination. Discussion: Our findings demonstrate that the OCV campaign in the FDMN camps were successful, reaching over 90% coverage, while coverage in the host community was much lower. To make sure that OCV vaccination efforts are reaching the target population and having the desired impact, our study emphasizes the need to inform the target population when the vaccination campaign will occur and where to get their vaccination.